2016
DOI: 10.3109/01480545.2016.1143482
|View full text |Cite
|
Sign up to set email alerts
|

No systemic exposure of transtympanic heparin-binding epidermal growth factor like growth factor

Abstract: Context Heparin binding epidermal growth factor like growth factor (HB-EGF) is an emerging therapeutic for the regeneration of the tympanic membrane. Objective Our aim was to determine whether the doses of HB-EGF delivered in a sustained release hydrogel into a middle ear mouse model, would be measurable in the systemic circulation. We also aimed to observe, in the scenario that the intended dose was absorbed directly into the circulation, whether these levels could be measured above the background levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Compared with the self-healing group, applying a composite hydrogel scaffold in the perforated TM of rats showed that it can achieve an ideal effect, and the new tissue was well connected with the surrounding natural tissue; on the contrary, the self-healing group did not achieve complete repair and the new tissue was sticky and cloudy. Peter Luke Santa Maria et al (Maria et al, 2016) combined heparin with a growth factor to repair TM defect. Although the repair effect was achieved after 2 months, the recovery of function still needed 1-4 months, and the whole tissue regeneration and function improvement had taken for half year, which was too long.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the self-healing group, applying a composite hydrogel scaffold in the perforated TM of rats showed that it can achieve an ideal effect, and the new tissue was well connected with the surrounding natural tissue; on the contrary, the self-healing group did not achieve complete repair and the new tissue was sticky and cloudy. Peter Luke Santa Maria et al (Maria et al, 2016) combined heparin with a growth factor to repair TM defect. Although the repair effect was achieved after 2 months, the recovery of function still needed 1-4 months, and the whole tissue regeneration and function improvement had taken for half year, which was too long.…”
Section: Discussionmentioning
confidence: 99%